Effects of local and landscape environmental variables on avifauna abundance in forest fragments of Atlantic Forest in southeastern Brazil - Santos, Clarissa de Oliveira (2018)
Pristine Neotropical forests have been converted into agricultural lands. Shifts in the internal structure and external pressures on forest remnants affect bird assemblages that require specific resources for survival at different spatial scales. In this study, we verified the relative contribution of three spatial scales (local, immediate surroundings and landscape) on the abundance of birds in Atlantic forest fragments in south-eastern Brazil. We tested whether species that responded in a similar way to environmental variables are in the same foraging guild. We carried out this study through 44 fixed points in 18 fragments, in the buffer zone of a protected area. We sampled 15 environmental variables in three spatial scales; six site-specific, three at the immediate surrounds (buffer radius of 100m), and six at the landscape). We recorded 1724 individuals from 108 species between April 2017 and February 2018. We classified sampled species in 15 foraging groups. The unique fractions of local and landscape have affected bird abundance, but the exclusive immediate surroundings have not significantly influenced this variable. We have identified a pattern related to the effects of local scale only for insectivorous birds, but no pattern for the other foraging guilds linked to any other scales. Our study may support management practices in the studied sites, practices mainly improving the understory density and canopy height of the remaining patches of native forest.